Cyatheales (Polypodiopsida) do Corredor de Biodiversidade do Norte do Pará, Brasil - GÓES NETO, Luiz Armando de Araújo (2015)
This paper is part of a series where the lycophyte and fern species of the Biodiversity Corridor ofnorthern Pará State are presented, produced under the project "Diagnóstico da Biodiversidade das Unidades de ConservaçãoEstaduais do Mosaico Calha Norte, Estado do Pará". In this manuscript the taxonomic treatment of Cyatheales is presented with identification keys, illustrations, distribution, descriptions, and comments to the studied taxa. Two families (Cyatheaceae and Metaxyaceae), three genera (Cnemidaria, Cyathea, and Metaxya), eight species, and one variety are registered. Cyathea is the most representative genus with seven species.